Resequencing and Signatures of Selective Scans Point to Candidate Genetic Variants for Hair Length Traits in Long-Haired and Normal-Haired Tianzhu White Yak - Bao, Qi; Ma, Xiaoming; Jia, Congjun; Wu, Xiaoyun; Wu, Yi; Meng, Guangyao; Bao, Pengjia; Chu, Min; Guo, Xian; Liang, Chunnian; Yan, Ping (Frontiers in Genetics, 2022)
Tianzhu white yak is a rare local yak breed with a pure white coat in China. In recent years, breeders have discovered long-haired individuals characterized by long hair on the forehead in the Tianzhu white yak, and the length and density of the hair on these two parts of the body are higher than that of the normal Tianzhu white yak. To elucidate the genetic mechanism of hair length in Tianzhu white yak, we re-sequence the whole genome of long-haired Tianzhu White yak (LTWY) (n = 10) and normal Tianzhu White yak (NTWY) (n = 10). Then, fixation index (FST), θπ ratio, cross-population composite likelihood ratio (XP-CLR), integrated haplotype score (iHS), cross-population extended haplotype homozygosity (XP-EHH), and one composite method, the de-correlated composite of multiple signals (DCMS) were performed to discover the loci and genes related to long-haired traits. Based on five single methods, we found two hotspots of 0.2 and 1.1 MB in length on chromosome 6, annotating two (FGF5, CFAP299) and four genes (ATP8A1, SLC30A9, SHISA3, TMEM33), respectively. Function enrichment analysis of genes in two hotspots revealed Ras signaling pathway, MAPK signaling pathway, PI3K-Akt signaling pathway, and Rap1 signaling pathway were involved in the process of hair length differences. Besides, the DCMS method further found that four genes (ACOXL, PDPK1, MAGEL2, CDH1) were associated with hair follicle development. Henceforth, our work provides novel genetic insights into the mechanisms of hair growth in the LTWY.